유산균에 의한 김치 중 N-Nitrosodimethylamine과 그 전구물질의 함량 감소 - 김상현(Sang-Hyun Kim); 김성현(Sung Hyun Kim); 강경훈(Kyung Hun Kang); 김정균(Jeong Gyun Kim); 성낙주(Nak-Ju Sung); 임희경(Heekyung Lim); 정미자(Mi Ja Chung) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2017)
To investigate the effects of lactic acid bacteria (LAB), Lactobacillus sakei, Lactobacillus curvatus, and Lactobacillus brevis, commonly found in kimchi, on N-nitrosodimethylamine (NDMA) and its precursors such as nitrite, dimethylamine (DMA), nitrate, and biogenic amines, Baechu (Chinese cabbage) kimchi prepared with and without LAB and $NaNO_2$ was periodically monitored for 20 days to analyze concentrations of NDMA and its precursors. Control was amine and nitrite-rich kimchi. NDMA and its precursors were analyzed to determine differences in concentrations between LAB-fortified kimchi and the control. The amounts of NDMA, nitrite, DMA, and nitrate remaining in LAB-fortified kimchi were significantly reduced compared with those of control kimchi. In addition, biogenic amines were significantly lower in kimchi prepared with L. sakei, L. curvatus, and L. brevis. These results suggest that addition of LAB to the kimchi preparation would be a promising solution for production of NDMA-reduced kimchi. 김치에 함유된 N-nitrosodimethylamine(NDMA) 및 그 전구물질들인 아질산염, dimethylamine(DMA), 질산염 그리고 biogenic amines 함량에 L. sakei, L. curvatus, L. brevis가 미치는 영향력을 알아보기 위해 아민류(젓갈)와 아질산염($NaNO_2$ 첨가)이 풍부한 김치에 유산균을 접종하여 20일 동안 저장하면서 NDMA와 그 전구물질의 함량 변화를 알아보았다. 유산균을 접종한 김치 중 NDMA, 아질산염, DMA, 질산염 함량이 대조군과 비교하여 현저히 감소하였다. 더하여 biogenic amines도 L. sakei, L. curvatus, L. brevis를 접종한 김치에서 현저히 감소하였다. 이들 결과는 유산균을 김치에 접종하는 것이 NDMA 저감화 김치 생산을 위한 해결책이 될 수 있으리라는 것을 제시하였다.